Contribution of Tau Pathology to Mitochondrial Impairment in Neurodegeneration - Pérez, María J.; Jara, Claudia; Quintanilla, Rodrigo A. (Frontiers in Neuroscience, 2018)
Tau is an essential protein that physiologically promotes the assembly and stabilization of microtubules, and participates in neuronal development, axonal transport, and neuronal polarity. However, in a number of neurodegenerative diseases, including Alzheimer´s disease (AD), tau undergoes pathological modifications in which soluble tau assembles into insoluble filaments, leading to synaptic failure and neurodegeneration. Mitochondria are responsible for energy supply, detoxification, and communication in brain cells, and important evidence suggests that mitochondrial failure could have a pivotal role in the pathogenesis of AD. In this context, our group and others investigated the negative effects of tau pathology on specific neuronal functions. In particular, we observed that the presence of these tau forms could affect mitochondrial function at three different levels: (i) mitochondrial transport, (ii) morphology, and (iii) bioenergetics. Therefore, mitochondrial dysfunction mediated by anomalous tau modifications represents a novel mechanism by which these forms contribute to the pathogenesis of AD. In this review, we will discuss the main results reported on pathological tau modifications and their effects on mitochondrial function and their importance for the synaptic communication and neurodegeneration.